P112 CPAP role on the perioperative outcomes of patients with obstructive sleep apnoea. (12th November 2015) - Macavei, VM; King, D; Sumpter, J; Berger, M; Mohr, OE; Mitic, J; O'Shaughnessy, TC
Abstract : Background: Obstructive sleep apnoea (OSA) has been previously reported as an independent risk factor for intra and post operative adverse events. 1 Early diagnosis of sleep disordered breathing and initiation of CPAP treatment was suggestive to improve operative outcomes. 2 Objectives: To determine the prevalence of sleep apnoea in a surgical population and establish the role of CPAP on peri-operative outcomes in patients with OSA. Methods: A retrospective study was performed in a university hospital between 1 st June 2013 and 1 st June 2015 and included 160 surgical patients investigated for OSA. Sleep apnoea was defined as dip rate >10 events/hour associated with a desaturation of 4% below the baseline. Statistical analysis was performed with STATA v10 software. Results: From 160 surgical patients included, 33.1% (53) were females and average age was 54 years. Prevalence of OSA was 44.3% (71/160) and 12.5% (20/160) had severe OSA defined as a dip rate >30 events/hour. Following sleep investigations, 68 patients had surgical interventions: 48.5% (33/68) trauma and orthopaedics, 17.6% (12/68) general surgery, 10.2% (7/68) urology, 8.8% (6/68) gynaecology, 7.3% (5/68) colorectal, 4.4% (3/68) ENT. From 68 patients undergoing surgical procedures, 44.1% (30/68) were diagnosed with OSA and started on CPAP prior to surgery. Peri-operative adverse events were not significantly related to OSA when compared to non OSA patients: intra operative desaturations (23.3% vs 26.3%) and prolonged recovery stay (53.3% vs 55.2%). OSA patients had a lower hospital stay compared to non OSA group (1.7 vs 3.1 days). Conclusions: We have identified a high prevalence of sleep apnoea of 44% in surgical population. CPAP treatment was found effective in improving operative outcomes of patients with OSA, further studies being needed to confirm these results. Routine pre-assessment screening for OSA followed by sleep investigations for initiation of CPAP prior to surgery is recommended. References: 1 Vasu TS, Grewal R, Doghramji K. Obstructive sleep apnoea syndrome and perioperative complications. J Clin Sleep Med . 2012;8 (2):199–207 2 Gross JB, et al . Practice guidelines for the perioperative management of obstructive sleep apnea: ASA task force on perioperative management of OSA. Anesthesiology 2014;120